Metodologi Penafsiran SaâÃd HawwÃ¢ Dalam Al-AsÃ¢s FÃ® Al-TafsÃ®r - Rohti, Wiwin Ainis (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2015)
This article examines the exegesis methodology of SaâÃ®d HawwÃ¢ in al-AsÃ¢s fÃ® al-TafsÃ®r. The book is the exegesis literature written in the paradigm of the unity of al-QurÃ¢n theme theory (al-Wahdah al-MawdÃ»âÃ®yah li al-QurâÃ¢n al-KarÃ®m). Methodological steps taken by HawwÃ¢ in realizing the goal of his interpretation are as follows: a) explaining the substance of suras (chapters) globally and the relationship among the suras in the context of the arrangement of the layout of al-QurâÃ¢n, b) displaying some verses based on their munÃ¢sabah groups, c) giving global understanding of each group of verses, d) describing the literal meaning of each verse, e) conducting explanatory of riwayat, f) analyzing issues regarding the suras and verses in the form of chapters, g) mentioning the important matters in the suras and verses concerning meanings, laws, wisdoms, and purposes of sharaâ contained in the verses, and h) describing the correlation of parts of al-QurÃ¢n in the context of the theory of al-Wahdah al-MawdÃ»âÃ®yah li al-QurâÃ¢n al-KarÃ®m.